Essential oils in the treatment of Phaseolus vulgaris L. seeds during storage - Leite, Keidima; Bonome, Lisandro Tomas da Silva; Moura, Gabriela Silva; Franzener, Gilmar (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Essential oils have secondary metabolites with antibacterial and antifungal properties. In this sense, the objective of this work was to evaluate the phytopathogen incidence and the physiological quality in seeds of Phaseolus vulgaris L. cv. BRS Splendor, treated with different essential oils in different packages and storage times. The essential oils of cinnamon (Cinnamomum zeylanicum), lemongrass (Cymbopogon citratus), clove (Syzgium aromaticum), lemon balm (Melissa officinalis), ginger (Zingiber officinale), sweet orange (Citrus sinensis), peppermint (Mentha piperita) and lemon-taiti (Citrus aurantifolia), commercial fungicide and the control, packed in kraft or pet. At 0, 60, 120 and 180 days after storage of the seeds, the water content were evaluated; first count of germination; percentage of germination; emergence of seedlings; speed germination index, dry matter and blotter test. The treatments with essential oils of C. aurantifolia and C. zeylanicum did not affect the percentage of germination of the seeds during the storage when packed in kraft packaging. At 120 and 180 days after storage, treatments with essential oils of C. aurantifolia and C. zeylanicum did not affect the percentage of germination of the seeds when packed in kraft packaging. There was a significant effect among the packages within the same storage period for the essential oils of C. zeylanicum; C.sinensis and M. officinalis that decreased the incidence of the fungus of the genus Aspergillus spp. The essential oils of C. zeylanicum and S. aromaticum decreased the incidence of Penicillium spp., both stored in pet, the essential oil of C. zeylanicum being similar to the commercial fungicide. The kraft packaging was more efficient in preserving the physiological quality of the treated seeds of Phaseolus vulgaris L. than the pet package. At zero storage time, treatments with C. sinensis and S. aromaticum promoted a negative effect on the physiological quality of the seeds compared to the control. The essential oil of C. citratus influenced negatively the percentage of germination of the seeds in relation to the other essential oils when stored in a kraft packaging.